Genetic estimation of correlations and causalities between multifaceted modifiable factors and gastro-oesophageal reflux disease - Sun, Yuanlin; Cao, Xueyuan; Cao, Donghui; Cui, Yingnan; Su, Kaisheng; Jia, Zhifang; Wu, Yanhua; Jiang, Jing (Frontiers in Nutrition, 2022)
Background: Gastro-oesophageal reflux disease (GORD) is a common gastrointestinal dysfunction that significantly affects the quality of daily life, and health interventions are challenging to prevent the risk of GORD. In this study, we used Mendelian randomization framework to genetically determine the causal associations between multifaceted modifiable factors and the risk of GORD. Methods: 66 exposures with available instrumental variables (IVs) across 6 modifiable pathways were included in the univariable MR analysis (UVMR). Summary-level genome-wide association studies (GWAS) datasets for GORD were retrieved from the Neale Lab (GORDNeale, Ncases=29975, Ncontrols=390556) and FinnGen (GORDFinn, Ncases=13141, Ncontrols= 89695). Using the METAL software, meta-analysis for single nucleotide polymorphisms (SNPs) from GORDNeale and GORDFinn was conducted with an inverse variance weighted (IVW) fixed-effect model. Moreover, we leveraged partition around medoids (PAM) clustering algorithm to cluster genetic correlation subtypes, whose hub exposures were conditioned for multivariable MR (MVMR) analyses. P values were adjusted with Bonferroni multiple comparisons. Results: Significant causal associations were identified between 26 exposures (15 risk exposures and 11 protective exposures) and the risk of GORD. Among them, 13 risk exposures (lifetime smoking, cigarette consumption, insomnia, short sleep, leisure sedentary behaviour (TV watching), body mass index (BMI), body fat percentage, whole body fat mass, visceral adipose tissue, waist circumference, hip circumference, major depressive disorder and anxious feeling), and 10 protective exposures (leisure sedentary behaviour (computer use), sitting height, hand grip strength (left and right), birth weight, life satisfaction, positive affect, income, educational attainment and intelligence) showed novel significant causal associations with the risk of GORD. Moreover, 13 exposures still demonstrated independent associations with the risk of GORD following MVMR analyses conditioned for hub exposures (educational attainment, smoking initiation and BMI). In addition, 12 exposures showed suggestive causal associations with the risk of GORD. Conclusions: This study systematically elucidated the modifiable factors causally associated with the risk of GORD from multifaceted perspectives, which provided implications for prevention and treatment of GORD.